INTI KONSILI VATIKAN II - Bohm, C.J. (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2018)
The Second Vatican Council showed a way to live a Christian life in today’s world. We select three items that merit to be given special attention to us who live 55 years after the Council: decentralization, the celebration of the Eucharist, and the mission of the lay faithful. Apart from these, we are invited to reflect on the central message of the Council, i.e. Jesus Christ himself.